2011
DOI: 10.1111/j.2158-1592.2011.01013.x
|View full text |Cite
|
Sign up to set email alerts
|

Examining Antecedents to Supply Chain Security Effectiveness: An Exploratory Study

Abstract: In recent years there has been increasing emphasis on managing risk and security in supply chains. Despite this emphasis, there have been relatively few empirical studies dealing with this issue. In an attempt to partially address this lack of empirical research, the primary purpose of this study was to explore the relationship between security management practices and the perceived effectiveness of supply chain security. With a resource‐based view of the firm and supply chain integration as theoretical underp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 34 publications
1
22
0
Order By: Relevance
“…Delineating between structural and motivation solutions enhances understanding of how PPPs can navigate social dilemmas because PPP supply chains may need to select either proactive or reactive solutions (Martens et al. ). A reactive structural solution may be socially costly, while a proactive motivational solution may prove impractical due to time constraints.…”
Section: Resolving Public‐private Partnerships Social Dilemmasmentioning
confidence: 99%
“…Delineating between structural and motivation solutions enhances understanding of how PPPs can navigate social dilemmas because PPP supply chains may need to select either proactive or reactive solutions (Martens et al. ). A reactive structural solution may be socially costly, while a proactive motivational solution may prove impractical due to time constraints.…”
Section: Resolving Public‐private Partnerships Social Dilemmasmentioning
confidence: 99%
“…This and other early work on the subject (e.g., Sheffi 2005a) foreshadowed some strong empirical work. Martens et al (2011) surveyed 62 executivelevel supply chain personnel and found that proactive security approaches, internal and external security planning, vulnerability of nodes, and measuring security performance are all significant influencers of security effectiveness. Their finding also indicates that the control variable of "firm type" leads to effectiveness outcomes and that firms involved in the food industry find lower levels of perceived security effectiveness than do firms in other industries.…”
Section: Scs Strategymentioning
confidence: 99%
“…This excellent study, while insightful, gives results only for the food industry and the findings may not apply elsewhere. In addition, Martens et al (2011) use food firms as a control variable in their research, which might indicate that food firms have lower levels of perceived security performance than do other firms. However, most firms and most industries have likely been affected by SCS, whether they welcome the effects or not; the number of security practices and government programs are evidence of this.…”
Section: Introductionmentioning
confidence: 99%
“…Lee, Seokgi (2006) emphasized the importance of adopting corporation certification standards and discussed the possibility of national and international standardization of customs/customs clearance through the introduction of C-TPAT in the U.S. and AEO in the EU. Lee Martens (2011) analyzed the perceived effect that security management customs have on supply chain security. His survey, which targeted logistics professionals, revealed that preventive measures are more effective than corrective measures while management support and sufficient access to resources play a greater role than other factors on supply chain security.…”
Section: Theoretical Backgroundsmentioning
confidence: 99%
“…1) These are divided into two categories: 'strategic items' and 'catch-all items'. The former refers to items that are designated and announced as export control items and the latter refers to dual-use items that have a high likelihood of being used for the manufacturing, development, deployment, and storage of WMD and the missiles that can be used to transport them 2) .…”
Section: Theoretical Backgroundsmentioning
confidence: 99%